Vehicle Load Capacity Analysis Above KMP. Swarna Kartika on Balikpapan – Palu Track - Yohan Wibisono; Paulina M Latuheru; Nyimas Andriani Shavitri Ardiansyah (IWTJ : International Water Transport Journal, 2022)
Kariangau Ferry Port which is managed and supervised by the Land Transportation Management Agency (BPTD) Region XVII of East Kalimantan and North Kalimantan Provinces serves 3 tracks, namely Kariangau - Penajam, Balikpapan - Palu, and Balikpapan - Mamuju. The Balikpapan – Palu track is 213 miles served by the Swarna Kartika Crossing Motor Boat (KMP. Swarna Kartika) operated by PT. Jembatan Nusantara with travel time ±20 hours. The distance traveled which takes a long time, it is necessary to pay attention to the security and safety conditions of the vehicles on board the ship. Currently, the arrangement and handling of vehicle loads on board the ship is still careless and positioned at a very close distance without rope safety (lashing) so that it is very dangerous for ship operators and vehicles on board. The method used to analyze existing problems is the analysis of the calculation of the load capacity of vehicles per group based on the Production Unit (SUP) in the Regulation of the Minister of Transportation Number 66 of 2019 concerning the Mechanism for Determining and Formulating the Calculation of Crossing Transportation Tariffs. Based on the results of the analysis, it was concluded that the average load factor of loading and unloading vehicles is very high, namely 139.49%. The ideal number of vehicle capacities on board KMP.Swarna Kartika is not yet suitable based on the Production Unit (SUP), where the SUP available vessels is smaller than the capacity of the used SUP. So that from this calculation, it is planned to arrange vehicles per group on the ship to match the SUP capacity available for the ship.